Education Financing Management at Islamic JHS Darul Mursydin West Pasaman - Simatupang, Umy Nadrah; Ridho, Muhammad; Gazali, Hamdani; Yahya, Yahya (International Journal of Educational Dynamics, 2023)
Education is a means of educating generations of students to gain quality knowledge. This is inseparable from the role of the principal as a manager in achieving the vision and mission of the school. To achieve the mission according to the targets that have been set, this is inseparable from education financing. Education financing is considered important because schools will not run massively if there is no education financing. Education financing itself has a function or use in realizing programs in schools, such as buying infrastructure, providing salaries or wages for teachers, conducting supervisory activities, and many more. It is known that the problem of financing education must always be felt in some schools. This is also the case at Darul Mursyidin Islamic Junior High School (JHS), which has a problem of inappropriate services based on the funds obtained by the school through student tuition and boss funds. This research discusses the management of education financing at Darul Mursyidin Islamic JHS in West Pasaman. The type of research used is through a qualitative approach and descriptive method, where one member of the author, has gone to the field first and seen the facts firsthand. The result is that Darul Musrsydin Islamic JHS in West Pasaman does need to make improvements by taking several steps to restore good quality education financing management for schools.